Progress and opportunities in Gellan gum-based materials - Gomes, D. (2023)
The authors acknowledge the support from FEDER funds through the POCI-COMPETE 2020–Operational Programme Competitiveness and Internationalisation in Axis I–Strengthening Research, Technological Development and Innovation (Project POCI-01-0145-FEDER-007491 ), from FCT –Fundação para a Ciência e Tecnologia. Publisher Copyright: © 2023 The Authors